LncRNA MALAT1 promotes migration and invasion of non-small-cell lung cancer by targeting miR-206 and activating Akt/mTOR signaling. Issue 8 (September 2018) - Tang, Yi; Xiao, GaoMing; Chen, YueJun; Deng, Yu
Abstract : Long noncoding RNA (lncRNA) metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ) functions as a crucial regulator of metastasis in lung cancer. The aim of this study is to unravel the underlying mechanisms of lncRNA MALAT1 in non-small-cell lung cancer (NSCLC). A cohort of 36 NSCLC tumor tissues and adjacent normal tissues was collected postoperatively from patients with NSCLC. qRT-PCR was performed to detect the expression of MALAT1 in both NSCLC tissues and cell lines. Cell migration and invasion were monitored by wound healing assay and transwell invasion assay. Western blot was used to detect the expression levels of epithelial–mesenchymal transition proteins and Akt/mTOR key components after treatment. Dual luciferase reporter assay coupled with qRT-PCR was used to verify the direct interaction between MALAT1 and miR-206 . MALAT1 was significantly up-regulated in both NSCLC tissues and cell lines. High expression of MALAT1 correlated positively with tumor size and lymphatic metastasis in NSCLC, whereas no correlation was found between MALAT1 expression and sex, age, clinical stage, and histological grade. We also showed that MALAT1 promoted epithelial–mesenchymal transition, cell migration, and invasion by activating Akt/mTOR signaling in A549 and H1299 cells. miR-206 was a direct downstream target of MALAT1 in NSCLC. MALAT1 promoted cell migration and invasion by sponging miR-206 in NSCLC cells. In addition, miR-206 inhibited MALAT1 -mediated activation of Akt/mTOR signaling in A549 and H1299 cells. lncRNA MALAT1 promotes migration and invasion of NSCLC by targeting miR-206 and activating Akt/mTOR signaling.